The naked liturgist - Church without a building for people without a house - Mostert, Martin (Stellenbosch Theological Journal, 2019)
The concept of "public" (as used in the termpublic worship) is interrogated in the light of Paul's understanding of nakedness/clothedness in 2 Corinthians 5:1-11. The conclusion drawn is that Christian liturgy is actually "private", and the resulting dissonance between precept and practice is untenable. A more appropriate approach to public-ness is developed with reference to John Wesley: liturgical events should and could intentionally be convened outside Christian premises - with the liturgists stripped of privilege. This is then illustrated by reference to field notes of an actual instance of such a "naked liturgy" that takes place weekly on the streets of Cape Town.